Thermo-mechanical modeling and transient analysis of frictional braking of elevator safety gear. Issue 12 (6th October 2020) - Wu, Aizhong; Shi, Xi; Weng, Lin; Hu, Dingyu
Abstract: Safety gear is one of the most important devices of elevators for its core function is to brake the over-speed cabin with friction. The frictional braking of elevator safety gear is a fully coupled thermo-mechanical process, and therefore both the thermal performance and the mechanical properties during braking should be comprehended for the tribological design of a high-speed elevator safety gear. In this work, a fully coupled model is developed to investigate the thermo-mechanical behaviors during emergency braking of a progressive safety gear. In the proposed model, the frictional sliding during braking is treated as the interfacial failure of the contact surface, and the transient thermo-mechanical analysis is performed using the explicit scheme. With the developed model, the contact temperature, the braking deceleration, the stress and deformation are examined. The analysis shows that the predicted temperature at the check points is consistent with results of experiment, and the simulated braking deceleration agrees well with the test results. The developed model can be utilized to simulate the braking performance of safety gear for a high-speed elevator.